Weight-Related Concerns as Barriers to Exclusive Breastfeeding at 6 Months. (May 2019) - Zimmerman, Emily; Rodgers, Rachel F.; O'Flynn, Jennifer; Bourdeau, Althea
Background: Human milk is considered the gold standard for infant nutrition, but more data are needed that examine the constellation of weight-related concerns as barriers to exclusive breastfeeding. Research aims: The aim of this study was to examine how mothers' concerns regarding their own and their infants' weight, as well as disordered eating behaviors, were associated with breastfeeding self-efficacy and exclusive breastfeeding at 6 months. Methods: A prospective, quantitative, and self-report online survey design was used. Participants included 206 women (88.30% White, 59.20% with graduate degrees), with a mean age of 33.04 years ( SD = 4.31 years) and a mean prepregnancy body mass index (BMI) of 24.80 kg/m 2 ( SD = 5.50 kg/m 2 ), who had given birth within the past 6 months. Results: Participants who reported not exclusively breastfeeding at 6 months had significantly higher prepregnancy BMI ( p < .001), higher body dissatisfaction ( p = .003), more disordered eating ( p = .036), higher child weight concerns ( p < .001), and lower breastfeeding self-efficacy ( p < .001). Mediation modeling revealed a direct negative relationship between prepregnancy BMI and exclusive breastfeeding at 6 months ( p < .001). Indirect negative relationships between prepregnancy BMI and exclusive breastfeeding at six months via (a) body dissatisfaction, (b) disordered eating, and (c) child weight concern, as well as breastfeeding self-efficacy (entered as concurrent mediators), were all significant. Conclusions: Mothers' weight, body image and eating concerns, concern regarding their children's weight, and breastfeeding self-efficacy may constitute critical barriers to exclusive breastfeeding at 6 months. Interventions to improve breastfeeding duration and confidence should target maternal body image and eating concerns.